Climate Apartheid Challenging Religious Communities to Engage Climate Change and Its Intersecting Issues - Bowers, Nadine (2023)
Climate change, poverty and racism/xenophobia are interrelated and must be analysed from an intersectional perspective. The late SA Archbishop Desmond Tutu himself coined the term "climate apartheid", highlighting the fact that "people who are wealthy and have access to enough resources can anticipate and adapt to climate change, while people who are poor and who live in poor countries have less ability to do so" (Mc Carthy 2021). In unpacking the ways in which the undue impacts of climate change rest more heavily on people of colour and women, further arguments are made for the global situation of eco-injustice to be framed within an understanding of systemic environmental apartheid and its intersectional effects. Much like during the period of South African apartheid, many religious communities are silent and complicit in eco injustice due to pietism, passivity, and fundamentalist theology(ies). The call is, therefore, made for religious communities to mobilise against this state of affairs using the lessons learnt in other struggles for justice.
Keywords: Climate apartheid; Ecojustice; faith and climate change; race and climate change